Programming surface-enhanced raman scattering of DNA Origami-templated metamolecules - Zhou, Chunyang; Liu, Na (Nano letters, 2020)
DNA origami holds an unprecedented capability on assembling metallic nanoparticles into designer plasmonic metamolecules of emerging properties, including surface-enhanced Raman scattering (SERS). SERS metamolecules were produced by positioning nanoparticles in close proximity to each other on a DNA origami template for Raman enhancement. In earlier reports, SERS metamolecules were generally assembled into clusters containing small number of nanoparticles (2, 3, or 4) and thus had limited programmability over SERS. Herein, we expanded the structural complexity of SERS metamolecules by increasing the number of nanoparticles and by arranging them into sophisticated configurations. DNA origami hexagon tile was used as the assembling template to fabricate clusters consisting of 6, 7, 12, 18, and 30+ metallic nanoparticles. Programmable SERS was realized via controlling the size, number, or spatial arrangement of nanoparticles. We believe this method offers a general platform for fabricating sophisticated nanodevices with programmable SERS that may be applied to a variety of fields including plasmonics, nanophotonics, and sensing.